Association between estimated glucose disposal rate and preserved ratio impaired spirometry in adults - Lin, Tong; Jin, Shaofeng; Shen, Xingkai; Huang, Shanshan; Mao, Haiyan (Frontiers in Endocrinology, 2025)
BackgroundPreserved ratio impaired spirometry (PRISm) is a newly defined phenotype of lung function impairment, characterized by a normal FEV1/FVC ratio alongside an FEV1/0.8 < FEV1 predicted value. Previous studies have linked PRISm to various adverse clinical outcomes, but its association with insulin resistance, as indicated by estimated glucose disposal rate (eGDR), remains underexplored.MethodsA total of 13,661 participants were included in this analysis after excluding individuals with missing data on PRISm (n = 10,954) and eGDR (n = 5,827). The median eGDR for the overall sample was calculated, and differences in baseline characteristics between the PRISm and non-PRISm groups were assessed. Logistic regression models were employed to analyze the relationship between eGDR and PRISm, adjusting for various confounders. Subgroup analyses were conducted based on gender and age. Additionally, the restricted cubic spline analysis was used to evaluate the non-linear relationship between eGDR and PRISm, and ROC analysis was performed to determine the predictive accuracy of eGDR for identifying PRISm.ResultsParticipants in the PRISm group exhibited significantly lower median eGDR values compared to the non-PRISm group (9.92 vs. 12.01 mg/kg/min; P < 0.001), indicating greater insulin resistance. The weighted multivariable logistic regression analysis revealed that each unit increase in eGDR was associated with a 15.1% reduction in the odds of PRISm in unadjusted models, and 7.3% in fully adjusted models (OR = 0.927, 95% CI: 0.880–0.976; P = 0.005). Subgroup analyses demonstrated a stronger association between eGDR and PRISm in females and individuals over 40 years of age. The restricted cubic spline analysis indicated a significant non-linear relationship, with an optimal eGDR cutoff of 11.423 mg/kg/min identified via ROC analysis (AUC = 0.626), demonstrating modest predictive accuracy.ConclusionOur study demonstrates a significant inverse association between estimated glucose disposal rate (eGDR) and preserved ratio impaired spirometry (PRISm) among a diverse population of US adults. Participants with lower eGDR values exhibited a higher prevalence of PRISm, indicating greater insulin resistance and potential metabolic dysfunction. The findings suggest that eGDR may serve as a valuable marker for assessing the risk of PRISm, particularly among women and older adults.